Quandaries of the Small-District Superintendency - Ivory, G.; Hyle, A.; McClellan, R.; Acker-Hocevar, M. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Focused on the particular needs of superintendents of districts of fewer than ten thousand students, the chapters teach students critical frameworks for thinking through and addressing the problems and practices superintendents encounter daily, allowing them to form a detailed and practical understanding of administration and leadership.